2019
DOI: 10.3390/molecules24224076
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Forchlorfenuron on the Morphology, Metabolite Accumulation, and Transcriptional Responses of Siraitia grosvenorii Fruit

Abstract: Siraitia grosvenorii fruit, called luo-han-guo (LHG), have been used as a traditional Chinese medicine (TCM) and dietary supplements for many years. Mogrosides, the main bioactive ingredients in LHG, are commercially available worldwide as a non-sugar-based and noncaloric sweetener. However, the production cannot meet the increasing market demand because of the low content of mogrosides and the small size of LHG. Therefore, some advanced technologies have been applied for improving the quality of LHG. Forchlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…A previous study just reported that high forchlorfenuron concentrations promote cucurbitacin B accumulation and biosynthesis in the melon fruit by activating the fruit-specific bitterness regulator CmBt . The Shi et al study found that the different expressions of SgUGTs would affect the accumulations and proportions of mogrosides in Siraitia grosvenorii induced by forchlorfenuron . However, the relationship between forchlorfenuron treatment and the arvenin I content was ignored in previous research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study just reported that high forchlorfenuron concentrations promote cucurbitacin B accumulation and biosynthesis in the melon fruit by activating the fruit-specific bitterness regulator CmBt . The Shi et al study found that the different expressions of SgUGTs would affect the accumulations and proportions of mogrosides in Siraitia grosvenorii induced by forchlorfenuron . However, the relationship between forchlorfenuron treatment and the arvenin I content was ignored in previous research.…”
Section: Resultsmentioning
confidence: 99%
“…7 The Shi et al study found that the different expressions of SgUGTs would affect the accumulations and proportions of mogrosides in Siraitia grosvenorii induced by forchlorfenuron. 31 However, the relationship between forchlorfenuron treatment and the arvenin I content was ignored in previous research.…”
Section: Effect Of the Forchlorfenuron On The Cucurbitacin Content In...mentioning
confidence: 99%
“…Zhu et al conducted a study on the developmental toxicity of CPPU administered to rats via gavage prenatally and postnatally. They found that CPPU may promote estradiol secretion, resulting in altered vaginal opening and first estrus time in prepubertal female rats [ 3 ]. These studies suggest that CPPU has potent effects on animal reproduction and development.…”
Section: Resultsmentioning
confidence: 99%
“…CPPU has already been registered for use in many countries, including European Union countries, the USA, and China [ 1 ], and is widely applied in kiwifruit, watermelon, cucumber, and grape cultivation [ 2 ]. However, the excessive and inappropriate use of CPPU in recent years has led to concerns regarding its safety [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Siraitia grosvenorii contains many cucurbitane triterpenoids (Niu et al, 2017;Qiao et al, 2019), which are sweet or slightly sweet substances (Shi et al, 2019). The…”
Section: Nutrients In Siraitia Grosvenorii and Their Functionsmentioning
confidence: 99%